The Effect of Local Government Revenue and Capital Expenditures on Economic growth - Gusnandar Arnan, Sendi; Oki Dewa Brata, Ignatius; Mulyati, Yati (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine how the influence of local government revenue and capital expenditure on economic growth in west java province period 2014-2018. The factors tested in this study are local government revenue and capital expenditure as an independent variable, while economic growth is the dependent variable. The method used in this research is descriptive analysis method to process and analyze the data obtained and to make a conclusion of the study. Data obtained through the government's financial statements and reports of economic growth from 2014 through 2018. The author uses the method of linear regression, correlation coefficient, determination coefficient and hypothesis testing using F test for simultaneous and t test for partial. Based on this study concluded that local government revenues and capital expenditure affects to economic growth.